The native aortic valve reduces paravalvular leak in TAVR patients - Prisco, Anthony R.; Zhingre-Sanchez, Jorge; Mattison, Lars; Yannopoulos, Demetris; Raveendran, Ganesh; Iaizzo, Paul A.; Gurevich, Sergey (Frontiers in Physiology, 2022)
Background: Paravalvular leak (PVL) is a frequent TAVR complication. Prospective identification of patients who are likely to develop PVL after TAVR would likely lead to improved outcomes. Prior studies have used geometric characteristics to predict the likelihood of PVL development, but prediction and quantification has not been done. One of the reasons is that it is difficult to predict the mechanical deformation of the native diseased aortic valve prior to implantation of the prosthetic valve, as existing calcifications likely contribute to the seal between the prosthetic valve and the aortic annulus. However, the relatively amount the native valve plays in preventing PVL is unknown. Methods: A retrospective chart review was conducted identifying patients with mild or greater PVL. One patient who had substantial PVL was identified and a 3D printed (pre-TAVR) aortic root was created. Balloon-expandable TAVR stent frames were implanted within the 3D printed root and a new model was created. Using this geometry, computational fluid dynamics (CFD) simulations were done to quantify PVL. The PVL flow path was iteratively decreased to simulate the space occupied by a crushed native aortic valve and PVL was quantified. Results: PVL was found to decrease as the space occupying the PVL area increased, demonstrating that the native aortic valve contributes to reducing regurgitation. CFD simulations demonstrated that within the patient analyzed, the native valve occupies between 3 - 40% of the PVL pathway. Conclusion: A priori techniques that predict the development of post TAVR PVL should account for the native diseased valve as our simulations demonstrate that it plays a role in reducing PVL.